IDENTIFIKASI SEBARAN JENIS TUMBUHAN KAYU TINGKAT TIANG DAN POHON BERDASARKAN KETINGGIAN TEMPAT DI BUKIT PANDAMARAN KHDTK ULM MANDIANGIN PROVINSI KALIMANTAN SELATAN - Tirsha Putri Ariefianti; Yusanto Nugroho; Damaris Payung (Universitas Lambung Mangkurat, 2022)
The introduction and analysis of vegetation that grows in nature such as Pandamaran Hill in the KHDTK area of Lambung Mangkurat University is important so that forest utilization can be carried out optimally. The way to identify vegetation types is by identifying plant morphological features. This study aims to identify the distribution of pole and tree-level woody plant species and analyze the types of pole and tree-level stands in Pandamaran Hill. The research method uses vegetation analysis by sampling to obtain the Important Value Index (INP), Species Diversity Index (H'), Type Evenness Index (e), Dominance Index (C), Community Similarity Index (IS), RAL for the ANOVA test of the influence of place height on the number of plants and identification of pole and tree level plant species. The vegetation analysis plot used is 20 m x 20 m, in it there is a plot measuring 10 m x10 m which is made as many as 3 paths with a division per height down (125-150 Masl), middle (150-175 Masl), upper (175-200 Masl) each 6 plots per path so that a total of 18 plots for 3 paths. The results of this study show that the highest INP value is dominated by types, H value' level of poles and trees per height of the place is classified as medium, the value of e level of poles and trees per height of the place is classified as almost evenly distributed, the value of C the level of poles and trees per height of the place is classified as medium-high, the ANOVA test with an interval of 25 masl for the influence of the height of the place on the number of plants does not differ markedly and For the identification of plant species, 10 types of poles and 19 types of trees with their respective distributionsPengenalan dan analisis vegetasi yang tumbuh di alam seperti Bukit Pandamaran kawasan KHDTK Universitas Lambung Mangkurat menjadi hal yang penting agar pemanfaatan hutan dapat dilakukan dengan optimal. Cara pengenalan jenis vegetasi yaitu dengan mengidentifikasi ciri morfologi tumbuhan. Penelitian ini bertujuan untuk mengidentifikasi sebaran jenis tumbuhan kayu tingkat tiang dan pohon serta mengalisis jenis tegakan tingkat tiang dan pohon yang ada di Bukit Pandamaran. Metode penelitian menggunakan analisis vegetasi secara sampling untuk mendapatkan Indeks Nilai Penting (INP), Indeks Keanekaragaman jenis (H’), Indeks Kemerataan jenis (e), Indeks Dominansi (C), Indeks Kesamaan Komunitas (IS), RAL untuk uji ANOVA pengaruh ketinggian tempat terhadap jumlah tumbuhan dan identifikasi jenis tumbuhan tingkat tiang dan pohon. Plot analisis vegetasi yang digunakan berukuran 20 m x 20 m, didalamnya ada plot ukuran 10 m x10 m yang dibuat sebanyak 3 jalur dengan pembagian per ketinggian bawah (125-150 Mdpl), tengah (150-175 Mdpl), atas (175-200 Mdpl) masing-masing 6 plot per jalur sehingga total 18 plot untuk 3 jalur. Hasil dari penelitian ini menunjukkan nilai INP tertinggi didominasi jenis, nilai H’ tingkat tiang dan pohon per ketinggian tempat tergolong sedang, nilai e tingkat tiang dan pohon per ketinggian tempat tergolong hamper merata, nilai C tingkat tiang dan pohon per ketinggian tempat tergolong rendah, nilai IS tingkat tiang dan pohon per ketinggian tempat tergolong sedang-tinggi, uji ANOVA dengan interval 25 Mdpl untuk pengaruh ketinggian tempat terhadap jumlah tumbuhan tidak berbeda nyata dan untuk identifikasi jenis tumbuhan mendapatkan 10 jenis tiang dan 19 jenis pohon dengan persebarannya masing-masing